Reversible acetylcholinesterase inhibitory effect of Tabernaemontana divaricata extract on synaptic transmission in rat CA1 hippocampus - Pratchayasakul W. (2014)
Background & objectives: Acetylcholinesterase inhibitors (AChE-Is) are used for the treatment of Alzheimer's disease (AD). These drugs including galanthamine have been shown to modulate synaptic activity in hippocampus and improve memory processes. Although Tabernaemontana divaricata extract (TDE) has been used as traditional medicine for various pharmacological effects, its effect in enhancing cholinergic activity provides additional benefit to its known effects. We investigated whether TDE can modulate the synaptic function in hippocampus and compared its effects to those of galanthamine. Methods: Hippocampal slices were prepared from male Wistar rats, functional effects of TDE were characterized by using pharmacological tools and extracellular recordings of field excitatory postsynaptic potentials (fEPSPs). Results: TDE significantly reduced fEPSPs. The fEPSPs reduction was prevented by atropine, but not pancuronium. These TDE effects were similar to those of galanthamine. Interpretation & conclusions: Our findings indicate that TDE can effectively modulate synaptic responses in the hippocampus similar to galanthamine, suggesting that this traditional medicine could be beneficial in ageing with ACh deprivation in the brain.